Avaliação da atividade anti-inflamatória e/ou antinociceptiva de duas espécies vegetais do cerrado: Lafoensia pacari A. St. Hil e Spiranthera odoratissima A. St. Hil. - Nascimento, Marcus Vinícius Mariano (2011)
The species of plants Lafoensia pacari A. St.-Hil and Spiranthera odoratissima A. Hil St., known as “pacarí” and “manacá”, respectively, are largely used in folk medicine in the state of Goiás, Brazil. This work shows the antinociceptive and anti-inflammatory effects of ethanolic extract of stem bark of “pacarí” (PEtExt) at doses of 100, 300 and 1000 mg/kg, p.o., in different models “in vivo” in mice, such as: acetic acid-induced abdominal writhing, croton oil–induced ear edema and formalin test. After the crude extract partitioning, only the ethyl acetate fraction at dose 640 mg/kg, p.o., (EAF) showed these activities. Ellagic acid at doses of (10, 30 and 100 mg/kg, p.o.) isolated from the stem bark of “pacarí”, is the substance responsible for the anti-inflammatory activity of PEtExt and EAF, however, the ellagic acid did not show antinociceptive effect on neurogenic pain formalin test. This antinociceptive activity does not involve the participation of opioid receptors, because it was not reversed by pretreatment with naloxone at dose 3 mg/kg, s.c., (opioid receptor antagonist). The results show that PEtExt and EAF have independent analgesic activity of anti-inflammatory effect of ellagic acid. This work also shows the anti-inflammatory of methanol/aqueous phase of the ethanol extract of the leaves of “manacá” at doses of 50, 150 and 500 mg/kg, p.o., (MAP) in different models “in vivo” in mice, such as: formalin test, carrageenan-induced paw oedema. Myeloperoxidase activity, capillary permeability, leukocyte migration and TNF-α levels were evaluated in pleural exudate. The reduction in the levels of TNF-α caused by treatment with MAP may be responsible for anti-inflammatory effect observed with the “manacá” plant in different models used.